Observation of clusters in Re60Fe30Al10 alloys and the associated magnetic properties - Ding, Jun (2012)
Magnetic properties and microstructure of melt-spun ribbons of RE60Fe30Al10 alloys with RE = Nd, Sm, Dy, Gd and Y were studied in detail. High coercivity values in the range of MA m−1 were observed at low temperatures for amorphous ribbons. Presence of Fe-rich clusters and nanoscale rare-earth crystallites in the amorphous matrix in the ribbons were revealed by high-resolution transmission electron microscopy studies. The magnetic transition temperatures were estimated experimentally and compared with fitting results based on the cluster ferromagnetism model (Wang L et al 2001 Phys. Rev. B 64 214410). Possible mechanisms for the magnetic behaviour observed due to the presence of Fe-rich magnetic clusters are discussed.